Generalizability of the EAST-AFNET 4 trial: assessing outcomes of early rhythm-control therapy in patients with atrial fibrillation. (14th October 2021) - Dickow, J; Van Houten, H.K; Sangaralingham, L.R; Friedman, P.A; Packer, D.L; Kirchhof, P; Noseworthy, P.A; Yao, X
Abstract: Background: The Early Treatment of Atrial Fibrillation for Stroke Prevention Trial (EAST-AFNET 4) demonstrated clinical benefit of early rhythm-control therapy in patients with recently diagnosed atrial fibrillation (AF) and concomitant cardiovascular conditions (CHA2DS2-VASc-Score ≥2) compared to the current practice of limited rhythm-control therapy to improve AF-related symptoms. Purpose: To evaluate the generalizability of the EAST-AFNET 4 trial in routine practice, we assessed the proportion of patients who would have met trial eligibility and examined the association between early rhythm-control and clinical outcomes. Methods: Using a large US administrative database, we identified 109, 739 patients with newly diagnosed AF from July 28th, 2011 to December 30th, 2016, the enrollment period of the EAST-AFNET 4 trial. Eligibility for trial inclusion was assessed based on inclusion criteria. Eligible patients were classified as either receiving early rhythm-control, i.e AF ablation and/or any antiarrhythmic drug therapy, within the first year after AF diagnosis (N=27, 106) or patients not receiving early rhythm-control (N=82, 633). The date 12 months after the first AF diagnosis was defined as the index date and the start of the follow up period. Propensity score overlap weighting was used to balance patients on 90 baseline characteristics. Cox proportional hazards regression was used to compare early rhythm-control with no early rhythm-control for the primary outcome of a composite end point of all-cause mortality, stroke, or hospitalization with the diagnoses heart failure or myocardial infarction. Results: Eligible for the trial were 72.9% (82, 633/109, 739) of all patients with newly diagnosed AF. Early rhythm-control therapy was associated with a reduction in the composite end point in the overall cohort of patients (hazard ratio [HR] 0.85; 95% confidence interval [CI] 0.75–0.97; P=0.015) with largely consistent treatment effects between patients eligible or ineligible for the trial. The reduction of stroke risk associated with early rhythm-control therapy was found in the overall cohort (HR 0.66; 95% CI 0.47–0.93; P=0.017) and in the trial-eligible cohort (HR 0.67; 95% CI 0.45–0.98; P=0.041). Conclusion: In a large health care data set, the majority of patients with newly diagnosed AF were eligible for the trial. Early rhythm-control therapy was associated with a 15% reduction in the composite end point of all-cause mortality, stroke, or hospitalization with the diagnoses heart failure or myocardial infarction, with the greatest benefit in the reduction of stroke risk. The treatment effect was consistent between patients eligible or ineligible for the trial. Patients in routine practice had higher rates of adverse outcomes than the trial, but the relative risk reduction with early rhythm-control therapy was similar. These data demonstrate the potential of early rhythm-control therapy to reduce outcomes in patients with AF. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): German Heart Foundation (Mit Fördermitteln der Deutschen Herzstiftung e.V.)